Peran Good Corporate Governance Dalam Mencegah Kecurangan (FRAUD) Pada Industri Perbankan - Ahmad Wahyudi Zein; Keisya Putri Balqis; Alya Arianti Nasution; Indah Tri Sari Harahap (Journal Of Informatics And Busisnes, 2026)
The banking industry has a strategic function when supporting financial stability, so its management is required to be held openly and accountably. The implementation of Good Corporate Governance as a framework is necessary when strengthening public trust and reducing the potential for the presence of fraudulent practices. This article aims to understand the role of Good Corporate Governance in fraud prevention efforts in the banking sector. The method used is a qualitative descriptive approach by reviewing various academic literature including scientific journals and relevant books. The results of the discussion show that the principles of Good Corporate Governance have a role in strengthening the internal control system, increasing accountability, and creating a culture of organizational ethics. The conclusion of the article emphasizes that Good Corporate Governance is a strategic instrument in building banking governance with health, integrity, and sustainability in order to maintain public trust and encourage the stability of the national financial system. This approach also shows a conceptual overview with the overall importance of governance, supervision, compliance, and organizational responsibility when reducing the risk of banking fraud in a systematic and sustainable manner.